Coconut shell extract imparting multifunction properties to ligno-cellulosic material. (February 2018) - Teli, Mangesh D; Pandit, Pintu; Basak, Santanu
Flame retardant textiles are increasingly in demand. There have been a number of approaches by which textile material is made flame retardant. The plant extracts imparting such properties to lingo-cellulosic material has been studied in this work. The paper reports the application of green coconut ( Cocosnucifera Linn) shell extract which is a natural waste source onto jute fabric. The acidic coconut shell extract was applied in neutral and alkaline conditions on jute fabric in different concentrations. The emerging fabric showed good flame retardant properties which were measured by different standard flammability tests. The limiting oxygen index value found to increase by 48% after application of alkaline coconut shell extract as such and on concentrating the coconut shell extract, it was found to increase 81%. The thermo gravimetric behaviour and degradation mechanism were studied by using thermo gravimetric analysis in nitrogen atmosphere. The presence of different elements, chemical groups and the structural topography of the untreated and coconut shell extract-treated lingo-cellulosic fabric were analysed by attenuated total reflection-Fourier transform infrared, Scanning electron microscopy, energy dispersive X-ray analysis and phytochemical analysis tests. In addition to the flame retardant property, the treated fabric showed natural colour (measured by colour strength value) and antibacterial property against both gram positive and gram negative bacteria.